Validation of the French version of the ICHOM adult oral health standard set. Issue 1 (23rd November 2022) - Nicolas‐Boluda, Alba; Simon, Stephane
Abstract: Introduction: The ICHOM Adult Oral Health Standard Set (AOHSS) recently developed by the ICHOM Oral Adult Health Working Group is a standard set of outcomes designed for its collection in clinical practice in dental health. The outcome standard set is made up of clinical‐reported outcome measures (CROMs) and patient‐reported outcome measures (PROMs). The purpose of this study was to translate and cross‐culturally adapt the PROM section of the Standard Set in French for France to enable comprehensive evaluation of the patients' oral health quality of life in a French population. Methods: The questionnaire was translated following the guidelines of the International Society for Pharmacoeconomics and Outcome Research (ISPOR). We included patients consulting in a dentistry clinic ( n = 127) and seeking dental care. The PROM and CROM data were collected from all patients. Both reliability and the internal consistency were evaluated. Results: The ICHOM AOHSS was successfully translated into French. We sampled and surveyed 126 patients in a dentistry clinic in France using the French translation of the ICHOM AOHSS. Cronbach's α was calculated to measure the internal consistency. The resulting Cronbach's α was 0.8, indicating acceptable homogeneity. Conclusions: The French version of the ICHOM AOHSS shows acceptable psychometric properties in terms of reliability and internal consistency. This translation is suitable for its implementation in a French‐speaking patient population.